2007
DOI: 10.1007/s10806-006-9023-8
|View full text |Cite
|
Sign up to set email alerts
|

Developing the ethical matrix as a decision support framework: GM fish as a case study

Abstract: The Ethical Matrix was developed to help decision-makers explore the ethical issues raised by agri-food biotechnologies. Over the decade since its inception the Ethical Matrix has been used by a number of organizations and the philosophical basis of the framework has been discussed and analyzed extensively. The role of tools such as the Ethical Matrix in public policy decision-making has received increasing attention. In order to further develop the methodological aspects of the Ethical Matrix method, work was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 5 publications
0
66
0
1
Order By: Relevance
“…Among others, the Ethical Matrix has been recently used for ethically assessing fisheries (Kaiser and Forsberg 2001) and for ethical evaluation of GM Fish production (Kaiser et al 2007). …”
Section: Methodology For Examination Of Aquaculture-related Ethical Imentioning
confidence: 99%
“…Among others, the Ethical Matrix has been recently used for ethically assessing fisheries (Kaiser and Forsberg 2001) and for ethical evaluation of GM Fish production (Kaiser et al 2007). …”
Section: Methodology For Examination Of Aquaculture-related Ethical Imentioning
confidence: 99%
“…It could be argued that lower prices for animal proteins high in beneficial nutrients represents a considerable consumer benefit which will deliver advantages to public health, although this may not be such an important benefit given that early innovations are destined for more affluent countries (Menozzi, Mora, and Merigo 2012). Of potentially greater importance regarding consumer adoption is the issue of how moral and ethical concerns contribute to rejection of GM animals in food (Kaiser et al 2007). It is suggested that the principle of informed choice, through adoption and implementation of an effective traceability and labeling policy, will prove beneficial if and when products are released into the market.…”
Section: Contamination Of Fish By Environmental Pollutantsmentioning
confidence: 99%
“…The ethical matrix is a conceptual tool developed since the mid-1990s by Ben Mepham, a professor of bioethics at Nottingham University and then further applied to several case studies (Kaiser, Millar, Thorstensen, & Tomkins, 2007;Mepham, Kaiser, Thorstensen, & Millar, 2006). This conceptual tool has been used primarily in the food and agriculture sector in order to help decision-makers to reach shared agreements about ethically sensitive issues (e.g., the adoption of prospective and sometimes controversial technologies).…”
Section: Ethical Matrixmentioning
confidence: 99%